Preface - Fuchs, Christian (Yuqi Na: The Chinese Internet. Political Economy and Digital Discourse)

Media, Economy and Society: A Critical Introduction. - Christian, Fuchs

Grundlagen einer Ethik des Radikalen Digitalen Humanismus - Fuchs, Christian (Digitalisierte Massenkommunikation und Verantwortung)

Vincent Mosco’s Critical-Humanist Political Economy of Communication - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Critical Perspectives on Digital Capitalism: Theories and Praxis (tripleC: Communication, Capitalism & Critique)

Critical Theory Foundations of Digital Capitalism: A Critical Political Economy Perspective - Fuchs, Christian (tripleC: Communication, Capitalism & Critique.)

Critical Perspectives on Digital Capitalism: Theories and Praxis. Introduction to the Special Issue - Fuchs, Christian; Arslan, Sevda Can; Allmer, Thomas (tripleC: Communication, Capitalism & Critique)

Der Tod und die Liebe: Die Metaphysik der Kommunikation - Fuchs, Christian (Soziale Ordnungen des Sterbens: Theorie, Methodik und Einblicke in die Vergänglichkeit)

Digital Ethics. Media, Communication and Society Volume Five - Fuchs, Christian

Der digitale Kapitalismus. Arbeit, Entfremdung und Ideologie im Informationszeitalter - Fuchs, Christian

Adorno and the Media in Digital Capitalism - Fuchs, Christian (Adorno und die Medien: Kritik, Relevanz, Ethik)

Universities and Academic Labour in Times of Precarisation and Digitalisation - Allmer, Thomas

Digital Democracy and the Digital Public Sphere - Fuchs, Christian

Zur Kritik der Politischen Ökonomie des Digitalen Kapitalismus: Die Aktualität von Manfred Knoches Beitrag zur Kritik der Politischen Ökonomie der Medien und der Kommunikation - Fuchs, Christian (Eigentum, Medien, Öffentlichkeit: Verhandlungen des Netzwerks Kritische Kommunikationswissenschaft)

The Problems of Base/Superstructure and Ideology in the Works of Stuart Hall, Georg Lukács, and Raymond Williams - Fuchs, Christian (The Communication Review.)
We live in times of deep crisis. General crises of society often are accompanied by ideological struggles. Given this context, it is important that social theory reinvigorates the analysis of ideology. For doing so, it makes sense to engage with classical theories of ideology. This paper contributes to this task. It asks: How are the economic and the non-economic related? What is ideology? This article deals with the base/superstructure problem and the problem of ideology via an engagement with selected aspects of Stuart Hall’s, Georg Lukács’s and Raymond Williams’s works. The commonality of Hall’s, Lukács’s and Williams’s thoughts that makes a joint engagement with their works feasible is that they all three dealt with aspects of culture from a critical theory perspective and are in one way or another representatives of Cultural Marxism. While Lukács’s works and Cultural Studies are often presented as conflicting approaches, this paper shows that concerning the question of how the economic and the non-economic are related and how we can think of ideology, the approaches of Lukács, Williams, and Hall complement each other, which allows critical theories of culture to draw on all three approaches and to combine elements from them in a synergistic manner. There are parallels between Williams’, Hall’s, and Lukács’s solutions to the base/superstructure problem. Williams argues that the economic exerts pressures on and sets limits to the non-economic. Hall writes that the economic determines the non-economic in the first instance. Lukács argues that the economic circumscribes subjectivity and the non-economic.
Keywords: base and superstructure; culture; economy and culture; Georg Lukács; ideology; Raymond Williams; Stuart Hall

Ibn Khaldûn and the Political Economy of Communication: A Reply to Graham Murdock - Fuchs, Christian (Critical Sociology)

Ibn Khaldûn and the Political Economy of Communication in the Age of Digital Capitalism - Fuchs, Christian (Critical Sociology)

Anmerkungen zum Begriff des digitalen Kapitalismus. - Christian, Fuchs (Theorien des digitalen Kapitalismus)

A Marxist-Humanist Perspective on Stuart Hall's Communication Theory - Fuchs, Christian (Theory and Society)

Grundlagen der Medienökonomie: Medien, Wirtschaft und Gesellschaft. - Fuchs, Christian

Verschwörungstheorien in der Pandemie - Fuchs, Christian

Social Media, Alienation, and the Public Sphere - Fuchs, Christian (The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media)

Digital Capitalism. Media, Communication and Society Volume Three - Fuchs, Christian

Digital Fascism. Media, Communication and Society Volume Four - Fuchs, Christian

Foundations of Critical Theory. Media, Communication and Society Volume Two - Fuchs, Christian

Marxism and Identity - Fuchs, Christian (Searching for a Self. Identity in Popular Culture, Media and Society)

Verschwörungstheorien in der Pandemie. Wie über COVID-19 im Internet kommuniziert wird - Fuchs, Christian

交往资本主义：迈向马克思主义交往理论的批判 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences))

数字资本主义和大数据时代的卢卡奇 - Fuchs, Christian (马克思主义与现实 (Marxism & Reality) 年第5期. (shortened article version))

数字、传播与社会主义 - Fuchs, Christian (国外理论动态 (Foreign Theoretical Trends))

社交媒体中的数字产消劳动：基于资本主义时间范畴的研究 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences) 2022 (4))

H παρακολούθηση των Κοινωνικών Μέσων - Fuchs, Christian (Η νέα ψηφιακή παρακολούθηση. Κείμενα προς τιμήν του Μηνά Σαματά (in Greek, The New Digital Surveillance: A Volume in Honour of Minas Samatas),)

Geburtstage: Manfred Knoche 80 Jahre - Fuchs, Christian (Publizistik)

Journalismus aus marxistischer Perspektive - Fuchs, Christian (Journalismustheorien)

Der Tod und die Liebe: Die Metaphysik der Kommunikation - Fuchs, Christian (Soziale Ordnungen des Sterbens)

Occupy the Internet: Why we need a Public Service Internet - Unterberger, Klaus; Fuchs, Christian (Building a European Digital Public Space: Strategies for Taking Back Control from Big Tech Platforms)

Social Media, Alienation, and the Public Sphere - Fuchs, Christian (The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media)

大数据、社交媒体和数字异化 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences) 2022 (5))

Servizio Pubblico - Fuchs, Christian (Wired Italia 102)

Digital Humanism. A Philosophy for 21st Century Digital Society. SocietyNow Series - Fuchs, Christian

Transform the Internet: Why we Need a Public Service Internet - Fuchs, Christian; Unterberger, Klaus (Public Value Texte)

The Public Service Media and Public Service Internet Utopias Survey Report - Fuchs, Christian (The Public Service Media and Public Service Internet Manifesto)

Communicating COVID-19. Everyday Life, Digital Capitalism, and Conspiracy Theories in Pandemic Times. SocietyNow Series - Fuchs, Christian

History and Class Consciousness 2.0: Georg Lukács in the Age of Digital Capitalism and Big Data - Fuchs, Christian (Information, Communication and Society)

Marxist Humanism and Communication Theory. Media, Communication and Society Volume One - Fuchs, Christian

Engels@200: Friedrich Engels and Digital Capitalism. How Relevant Are Engels’s Works 200 Years After His Birth? - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Engels@200: Friedrich Engels in the Age of Digital Capitalism. Introduction - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Cornel West and Marxist Humanism - Fuchs, Christian (Critical Sociology)

Das digitale Kapital. Zur Kritik der politischen Ökonomie des 21. Jahrhunderts - Fuchs, Christian

The Public Service Media and Public Service Internet Manifesto